The Implementation of Teaching Materials with a Synthetic Analytical Structure Model Using Canva to Improve Early Reading and Writing Skills in Grade 1 Elementary School Students - Supriyatin, Iyet; Samsudin, Asep; Septian Rahayu, Galih Dani (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to analyze the development process, feasibility, and effectiveness of teaching materials based on the Synthetic Analytical Structure model, assisted by the Canva application, in improving the early reading and writing skills of first-grade students, involving 10 students in the limited trial and 44 students in the extensive trial, as well as identifying obstacles faced by teachers and students. The research method uses a simplified Borg and Gall Research and Development model approach through the stages of needs analysis, product design, expert validation, revision, limited trials, extensive trials, and final product preparation. The results show that the teaching materials, Student Worksheets (LKPD), learning media, and Lesson Plans (RPP) are in the very feasible category. Students' reading ability has improved, indicated by the average score of the limited test from 7.6 to 13.5 and the extensive test from 7.43 to 12.09. Writing ability also increased significantly, from an average of 76.1 to 88.1 in the limited test and from 72.4 to 86.9 in the extensive test, with moderate N-gain scores of 0.41 in the limited trial and 0.51 in the extensive trial.. Interviews revealed student challenges with letter and word writing, and writing speed, as well as teacher challenges with limited learning time.  Therefore, SAS-based teaching materials with Canva proved effective as an interactive, systematic, and enjoyable alternative for early literacy learning.